2012
DOI: 10.3109/09273972.2012.735338
|View full text |Cite
|
Sign up to set email alerts
|

Specific Health-Related Quality of Life Concerns in Children with Intermittent Exotropia

Abstract: Purpose To assess the frequency of specific health-related quality of life (HRQOL) concerns in children with intermittent exotropia (XT) using the Intermittent Exotropia Questionnaire (IXTQ). Methods 80 children with intermittent XT (aged 5 to <17 years), plus one parent for each child, completed the Child and Proxy IXTQ respectively. Each item was scored from 0 to 100 (worst to best HRQOL). Mean scores were calculated for each item and items were ranked from lowest to highest impact (worst HRQOL). Analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
8
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 17 publications
3
8
0
2
Order By: Relevance
“…Furthermore, out of the items in the IXTQ, children with IXT were most bothered by the need to shut one eye in the sun and waiting for the eyes to clear up. Teasing and difficulty making friends were of least concern, in line with other studies that showed a surprising lack of teasing and bullying in children with strabismus 18. It is perhaps not surprising then that clinical measurements such as poorer control and larger angle of deviation which are more likely to lead to social bias are not necessarily correlated with poorer child IXTQ scores.…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, out of the items in the IXTQ, children with IXT were most bothered by the need to shut one eye in the sun and waiting for the eyes to clear up. Teasing and difficulty making friends were of least concern, in line with other studies that showed a surprising lack of teasing and bullying in children with strabismus 18. It is perhaps not surprising then that clinical measurements such as poorer control and larger angle of deviation which are more likely to lead to social bias are not necessarily correlated with poorer child IXTQ scores.…”
Section: Discussionsupporting
confidence: 81%
“…Even the questionnaires for quantifying HRQOL in childhood intermittent exotropia, e.g., "shutting one eye when sunny, waiting for their eyes to clear up, and worrying about their eyes", were designed to be clinically relevant [11,12]. However, few studies have evaluated the correlation between the severity of intermittent exotropia and HRQOL.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, younger children, who have not yet to form a clear aesthetic concept and an established awareness of their eye disease. Essentially, strabismus is their norm and has little effect on their daily life [26] . Moreover, exotropia in children with IXT appears intermittently, which may also make it di cult for them to consistently respond to this condition and would thus not always affect their quality of life.…”
Section: Discussionmentioning
confidence: 99%